2016
DOI: 10.2337/db16-0846
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Limits Diabetogenic CD8+ T-Cell Effector Responses in Type 1 Diabetes

Abstract: Type 1 diabetes development in the NOD mouse model is widely reported to be dependent on high-level production by autoreactive CD4+ and CD8+ T cells of interferon-γ (IFN-γ), generally considered a proinflammatory cytokine. However, IFN-γ can also participate in tolerance-induction pathways, indicating it is not solely proinflammatory. This study addresses how IFN-γ can suppress activation of diabetogenic CD8+ T cells. CD8+ T cells transgenically expressing the diabetogenic AI4 T-cell receptor adoptively transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
(55 reference statements)
1
28
0
Order By: Relevance
“…The ability of IFN-c to induce or promote T1D was found to be dependent on the dosage and time of interventions relative to the disease progression in NOD mice. 84 The protective role of IFN-c is associated with the suppression of diabetogenic CD8 + T-cell responses by inhibiting STAT1 expression 85 and with a decrease in Th1 cellrelated cytokines, particularly IL-12 and IL-2, in spleen cells (Table 1). 84 In some circumstances, IFN-c is a key participant in DC-or vaccine-mediated peripheral tolerance in T1D.…”
Section: Ifnsmentioning
confidence: 99%
“…The ability of IFN-c to induce or promote T1D was found to be dependent on the dosage and time of interventions relative to the disease progression in NOD mice. 84 The protective role of IFN-c is associated with the suppression of diabetogenic CD8 + T-cell responses by inhibiting STAT1 expression 85 and with a decrease in Th1 cellrelated cytokines, particularly IL-12 and IL-2, in spleen cells (Table 1). 84 In some circumstances, IFN-c is a key participant in DC-or vaccine-mediated peripheral tolerance in T1D.…”
Section: Ifnsmentioning
confidence: 99%
“…Greater insight into how human CD8 + T-cells utilize energy substrates will provide essential tools for other autoimmune disorders, in addition to T1D. Recent studies have shown how type 1 interferons alter the signaling pathways in both a mitochondrial dependent and independent manner 1016 , thus indicating an avenue of investigation to determine the effect of type 1 interferons in the inflammatory microenvironment upon human CD8 + T-cell metabolism 10 . With the ability to trace macronutrient usage during T-cell activity, we could alter metabolism to better understand how CD8 + T-cells require ATP and are able to better mimic the islet microenvironment, as well as providing greater insight for cancer or other immunotherapies and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen specific human CD8 + T-cells were produced as previously described 10,16 . All cultures were carried out in complete RPMI [cRPMI recipe: RPMI 1640 (Cellgro, Manassas, VA), supplemented with 10% FBS (HyClone, Fisher Scientific, Pittsburgh, PA), 1% MEM non-essential amino acids (Cellgro), 1% penicillin-streptomycin (Gemini Bio-Products, West Sacramento, CA) solution, 1% Glutamax (Cellgro), 1% sodium pyruvate (Cellgro), 0.004% 2-mercaptoethanol (Cellgro), and 10 mM HEPES (Cellgro)].…”
Section: Methodsmentioning
confidence: 99%
“…In all the analyses, our approach identifies the pathways related to IFNγ signalling and chemokinemediated signalling as enriched. IFNγ is produced by autoreactive CD4+ and CD8+ T cells [Driver et al, 2017] and is believed to play a key role in driving the autoimmune pathogenesis of T1D [Yi et al, 2012;Driver et al, 2017;Souto et al, 2014;Peakman, 2013;Clark et al, 2017;Bending et al, 2012;Borish et al, 2003], even though it is not considered solely a pro-inflammatory cytokine [Driver et al, 2017]. IFNγ also results in local up-regulation of chemotactic cues that induce immune cell migration to the islets, for instance via chemokine mediated signalling, where β-cells produce certain chemokines that can accelerate or block T1D progression [Clark et al, 2017].…”
Section: Discussionmentioning
confidence: 99%